Structural and functional brain correlates of the neutrophil- and monocyte-to-lymphocyte ratio in neuropsychiatric disorders - Roger McIntosh (Brain, Behavior, & Immunity - Health)
Skews in the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) increasingly demonstrate prognostic capability in a range of acute and chronic mental health conditions. There has been a recent uptick in structural and functional magnetic responance imaging data corroborating the role of NLR and MLR in a cluster of neuropsychiatric disorders that are characterized by cognitive, affective, and psychomotor dysfunction. Moreover, these deficits are mostly evident in setting of acute and chronic disease comorbidity implicating aging and immunosenescent processes in the manifestation of these geriatric syndromes. The studies reviewed in this special edition implicate neutrophil and monocyte expansion relative to lymphocytopenia in the sequelae of depression, cognitive and functional decline, as well as provide support from a range of neuroimaging techniques that identify brain alteartions concommitant with expansion of the NLR or MLR and the sequelae of depression, dementia, and functional decline.